EDUKASI PENCEGAHAN KANKER PAYUDARA MELALUI TEKNIK SADARI TERHADAP PENINGKATAN PENGETAHUAN DETEKSI DINI KANKER PAYUDARA PADA REMAJA - Rahel Charolina Putri; Yora Nopriani; Bela Purnama Dewi (Jurnal Kesehatan dan Pembangunan, 2026)
Bre~ast cance~r i~s one~ of the~ di~se~ase~s wi~th the~ hi~ghe~st i~nci~de~nce~ and mortali~ty rate~s i~n wome~n. E~arly de~te~cti~on through bre~ast se~lf-e~xami~nati~on (BSE~) i~s i~mportant to i~ntroduce~ from adole~sce~nce~ as a pre~ve~nti~ve~ me~asure~. Thi~s study ai~ms to de~te~rmi~ne~ the~ e~ffe~ct of bre~ast cance~r pre~ve~nti~on e~ducati~on through BSE~ te~chni~que~s usi~ng le~afle~ts on i~ncre~asi~ng knowle~dge~ of e~arly bre~ast cance~r de~te~cti~on among fe~male~ stude~nts at Bi~na Ci~pta Pale~mbang Hi~gh School. Thi~s study use~d a pre~-e~xpe~ri~me~ntal de~si~gn wi~th a one~-group pre~te~st–postte~st approach on 31 fe~male~ stude~nts se~le~cte~d usi~ng a total sampli~ng te~chni~que~. The~ re~se~arch i~nstrume~nt was a knowle~dge~ que~sti~onnai~re~. The~ re~sults of uni~vari~ate~ analysi~s showe~d that the~ ave~rage~ le~ve~l of knowle~dge~ of re~sponde~nts be~fore~ be~i~ng gi~ve~n he~alth e~ducati~on was 8.06 and i~ncre~ase~d to 12.35 afte~r be~i~ng gi~ve~n e~ducati~on, re~sulti~ng i~n an i~ncre~ase~ of 4.29. Thi~s analysi~s i~llustrate~s an i~ncre~ase~ i~n knowle~dge~ be~fore~ furthe~r te~sti~ng. The~ re~sults of the~ Shapi~ro–Wi~lk te~st showe~d that the~ data we~re~ normally di~stri~bute~d, and the~ Pai~re~d Sample~ t-te~st analysi~s showe~d a si~gni~fi~cant di~ffe~re~nce~ be~twe~e~n be~fore~ and afte~r e~ducati~on (p < 0.05). I~t was conclude~d that BSE~ e~ducati~on usi~ng le~afle~ts had an e~ffe~ct on i~ncre~asi~ng adole~sce~nt knowle~dge~. I~t i~s re~comme~nde~d that e~ducati~onal programs be~ carri~e~d out conti~nuously i~n schools as an e~ffort to de~te~ct bre~ast cance~r e~arly.